The implementation of family medicine approach of patients with hypertension, neurodermatitis, and obesity - Reagan Darmawan; Natasya; William Gilbert Satyanegara; Zita Atzmardina (Science Midwifery, 2023)
Diagnosis and management are carried out using a family medicine approach. Primary data were obtained through history, physical examination, supporting examinations and home visits. Secondary data from patient medical records from the Legok Health Center. Mrs. I, 44 years old with complaints of headache and itching in the left lower leg, blood pressure examination found 224/130 mmHg and BMI 31.16 kg/m2. The patient's internal factors are genetic factors, lack of knowledge about the disease, as well as behavior and daily habits. External factors include lack of family support and knowledge about the disease, economic factors, transportation limitation, and beliefs and culture. By using the family medicine approach, it was found that blood pressure decreased by 170/90 mmHg, complaints of headaches, itching and skin lesions on the left lower leg improved and losing weight about 2 kg in 4 weeks. Complex clinical problems require holistic and comprehensive management through a family medicine approach. Individual management is not only an intervention on clinical aspects but also solutions to problems in environmental aspects that affect an individual's health.